SARKASME JUDUL BERITA SURAT KABAR NASIONAL - Mahmudah Mahmudah (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
This study is a qualitative research with description design. The research data was sarcasm in the head line of Kompas and Fajar newspaper which determined by purposive sampling. Data collection was conducted during January-February 2011. The results showed that sarcasm of headlines in national newspapers going for violating the principles of courtesy, the maxims of wisdom, generosity, praise, humility, agreements, and sympathy. Diction sarcasm was categorized as harmful, inappropriate, no good, rough, and hard. Sarcasm that breaking notion that breaking faces, positive face and negative face